Five‐year follow up of a randomised controlled trial comparing subtotal with total abdominal hysterectomy. (11th June 2014) - Andersen, LL; Zobbe, V; Ottesen, B; Gluud, C; Tabor, A; Gimbel, H; ,
Abstract : Objectives: To compare the rates of urinary incontinence (UI) and other complications of subtotal abdominal hysterectomy (SAH) with total abdominal hysterectomy (TAH) at 5 years after surgery. Design: Randomised clinical trial with central, computer‐generated randomisation. Setting: Danish multi‐centre trial performed in 11 departments of gynaecology. Population: Women referred with benign uterine diseases scheduled for abdominal hysterectomy. Methods: Women were randomised to either SAH ( n  =   161) or TAH ( n  =   158). Follow‐up data were collected from participants using postal questionnaires sent out 5 years after surgery. Complications of hysterectomy were further examined by scrutinising registered discharge summaries following hospitalisation. Intention‐to‐treat and per‐protocol analyses were conducted. Potential bias caused by missing data was handled using multiple imputation. Main outcome measures: The primary outcome was UI. Secondary outcomes included constipation, prolapse of the vaginal vault or cervical stump, satisfaction with sexual life, pelvic pain, postoperative complications and vaginal bleeding. Results: The response rate was 234/319 (73.4%). A significantly higher proportion of respondents had urinary incontinence 5 years after SAH 34/113 (30.1%) than TAH 21/119 (17.6%) (RR 1.71, 95% confidence interval 1.06–2.75, P  = 0.026). This difference reduced after multiple imputation to account for missing data (RR 1.37, 95% confidence interval 0.99–1.89, P  = 0.052). Eleven of the 101 women (11%) in the SAH group still experienced vaginal bleeding. No other differences were found between the two types of abdominal hysterectomy. Authors' conclusions: A smaller proportion of women suffered from UI after TAH than after SAH 5 years postoperatively. Around one in ten women continued to experience vaginal bleeding 5 years after SAH.